2014
DOI: 10.1089/aid.2014.0106
|View full text |Cite
|
Sign up to set email alerts
|

The Immune Pathogenesis of Immune Reconstitution Inflammatory Syndrome Associated with Highly Active Antiretroviral Therapy in AIDS

Abstract: The present study investigated the immunological pathogenesis of immune reconstitution inflammatory syndrome (IRIS) in acquired immunodeficiency syndrome (AIDS) patients undergoing highly active antiretroviral therapy (HAART). A total of 238 patients with AIDS who received initial HAART were included in this prospective cohort study. Blood samples were collected immediately, at baseline, at week 12, and at week 24 after initial HAART and at the onset of IRIS. Lymphocyte subsets, Th1 and Th2 cytokines, and inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

2016
2016
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 18 publications
1
14
0
1
Order By: Relevance
“…Serum cytokines and/or chemokines have emerged as important players in the development of HICP in HCM patients in recent years, but the related findings are inconsistent. For example, a study by Boulware et al indicated that high serum pre-ART levels of IL-4 and IL-17 are predictive of future IRIS in HCM patients [11], whereas Zheng's research indicated that decreased IL-4 and IL-17 levels were associated with HICP during IRIS [12]. These paradoxical research findings indicate the need to investigate further the roles of cytokines/chemokines in HICP.…”
Section: Introductionmentioning
confidence: 99%
“…Serum cytokines and/or chemokines have emerged as important players in the development of HICP in HCM patients in recent years, but the related findings are inconsistent. For example, a study by Boulware et al indicated that high serum pre-ART levels of IL-4 and IL-17 are predictive of future IRIS in HCM patients [11], whereas Zheng's research indicated that decreased IL-4 and IL-17 levels were associated with HICP during IRIS [12]. These paradoxical research findings indicate the need to investigate further the roles of cytokines/chemokines in HICP.…”
Section: Introductionmentioning
confidence: 99%
“…Particularly due to high levels of IL-12, TNFα, IFNγ, Th1 responses are considered to associate with IRIS. Other studies suggested that the imbalance between anti-inflammatory T regulatory cells (T regs ) and pro-inflammatory Th17 cells may also play a role in IRIS [16, 1, 17]. However, albeit inflammatory, the role of Th17 cells, in IRIS is still largely elusive.…”
Section: Iris In Humansmentioning
confidence: 99%
“…Por otro lado, recientemente han sido observadas personas infectadas con una cepa recombinante de VIH (CXCR-4 o R4) que presentan una rápida evolución de la infección a etapas avanzadas (sida) en menos de 3 años. (38,39) El TARV ha reducido de manera importante la morbi-mortalidad en VIH/sida.…”
Section: Infección Crónica O Latencia Clínica Masunclassified